Behavior And Performance Of Steel Frame Structures With X-Type Concentric Bracing System Due To Variations In Comparison Of Span Width To Story Height (L/H) - I Nyoman Indra Kumara; I Gede Fery Surya Tapa; I Nengah Darma Susila (Logic : Jurnal Rancang Bangun dan Teknologi, 2023)
X-type bracing is the strongest bracing. The bigger ratio of the width of the span to the high level (L/H), the slope of the angle on the bracing will be more declivous. The analysis of the structure with the L/H ratio to determine the behavior of the structure using linear analysis of response spectrum and structural performance using the static nonlinear pushover analysis (ETABS 2016) to determine the displacement target that occurred in the structure. Structural modeling is done on 3D portals with levels of 3, 5, 8 and 10 floors with different L/H variations, including L/H=1; L/H=1.25; L/H=1.5; L/H=1.75; and L/H=2. Structural modeling is planned to be in the Surabaya area with moderate soil conditions. This study obtains data such as: (1) The largest maximum drift and floor drift are at type L/H=2, (2) The largest base shear force in the nonlinear pushover analysis at each story occurs at L/H=1, (3 ) In the yield condition type L/H=1 has the smallest percentage of structural stiffness, but in the ultimate condition type L/H=1 has the largest percentage of structural stiffness, and (4) The highest ductility value at each story occurs in type L/H=2 . Based on these results, it shows that the greater the type of L/H in the bracing structure, the greater the displacement target produced. If the angle of bracing becomes more sloping, then the displacement and target displacement that occurs increases.